Occurrence of Mycobacterium spp. and other pathogens in lymph nodes of slaughtered swine and wild boars (Sus scrofa) - Batista Lara, Gustavo Henrique [UNESP]; Ribeiro, Márcio Garcia [UNESP]; Fujimura Leite, Clarice Queico; Paes, Antonio Carlos [UNESP]; Guazzelli, Alessandro [UNESP]; da Silva, Aristeu Vieira; Barreto Santos, Adolfo Carlos [UNESP]; Paganini Listoni, Fernando Jose [UNESP] (Elsevier B.V., 2011)
Myco bacterium spp. and other pathogens were investigated in 258 swine lymph nodes (129 with and 129 without apparent lesions), and 120 lymph nodes (60 with and 60 without lesions) from wild boars (Sus scrofa). A total of lymph nodes from swine and wild boars were collected of different animals. Submaxillar and mesenteric lymph nodes were submitted to microbiological examination and colonies suggestive of Mycobacterium spp. (alcohol-acid bacilli) were submitted to PCR Restriction Assay (PRA). In swine with lymphadenitis. Mycobacterium spp. (24.1%) and Rhodococcus equi (13.2%) were the most prevalent microorganisms, while in lymph nodes without lesions were identified a complex of microorganisms, including of environmental mycobacteria. In wild boars with lymphadenitis, beta-haemolytic Streptococcus (10.0%), Mycobacterium spp (8.4%) and R. equi (6.6%) were the most frequent. Among mycobacterias were identified predominantly Mycobacterium avium subspecies type 1 (48.3%) and M. avium subspecies type 2 (16.1%), followed by Mycobacterium intracellulare, Mycobacterium szulgai, Mycobacterium fortuitum, Mycobacterium gordonae, Mycobacterium simiae, Mycobacterium nonchromogenicum and Mycobacterium intracellulare type 2. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Swine; Wild boars; Mycobacterium spp.; Rhodococcus equi; Lymph nodes; Brazil